2001
DOI: 10.1080/08037050152669729
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and Dopa Urinary Excretion in Patients with Pheochromocytoma–Diagnostic Implications

Abstract: Pheochromocytoma, a potentially life-threatening disease, is a rare cause of hypertension. Most pheochromocytomas secrete excessive amounts of noradrenaline and adrenaline. It has been suggested by some authors that high circulating levels of dopamine and the catecholamine precursor dihydroxyphenylalanine (dopa) are more often associated with malignant rather than benign pheochromocytomas. Therefore the aim of this study was to evaluate urinary excretion of dopamine and dopa in patients with pheochromocytoma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Although dopamine-secreting paragangliomas are often asymptomatic (9), excessive excretion of dopamine can cause complaints of nausea, vomiting, flushing, and orthostatic hypotension (18,19). We observed that the clinical manifestations in patients with increased 3-methoxytyramine excretion were different compared with those in patients with normal excretion of 3-methoxytyramine.…”
Section: Discussionmentioning
confidence: 79%
“…Although dopamine-secreting paragangliomas are often asymptomatic (9), excessive excretion of dopamine can cause complaints of nausea, vomiting, flushing, and orthostatic hypotension (18,19). We observed that the clinical manifestations in patients with increased 3-methoxytyramine excretion were different compared with those in patients with normal excretion of 3-methoxytyramine.…”
Section: Discussionmentioning
confidence: 79%
“…16,17 This may reflect predominant development of malignant pheochromocytomas from neural crest progenitors arrested in an early stage of development with a malignancy-prone lineage able to populate both adrenal and extra-adrenal sites of chromaffin tissue. The matching of gene expression profiles in neural crest progenitors with those in different groups of pheochromocytomas and mechanistic studies linking these progenitors to effects of specific genes provides possible approaches to test the foregoing hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed by David Goldstein, high plasma and urinary levels of dihydroxyphenylalanine and dopamine, the immediate precursors of norepinephrine, are biochemical hallmarks that may characterize malignant pheochromocytoma (Anton et al 1967, Goldstein et al 1986, John et al 1999, Januszewicz et al 2001, van der Harst et al 2002. While suggestive of a dedifferentiated state that might be associated with malignancy, these markers do not, however, accurately discriminate benign from malignant pheochromocytomas.…”
Section: Diagnostic and Prognostic Markersmentioning
confidence: 99%